Communication from the Auditing Board, relative to commutation of clothing, &c. &c. &c. - Munford, George Wythe, 1803-1882 (House document (Virginia. General Assembly. House of Delegates), 1863)
October 10, 1863 communications from the members of the Auditing Board in response to a report by the House committee on military affairs against the auditing board in regards to the commutation of clothing for state troops. The members of the Board explained the reasoning behind regulations, which the House committee considered unfair to some of the soldiers. This explanation was to clarify the Board's decisions and rules regarding when money would be given to state troops for clothing.